Maternal Mortality Levels and Trends in Nepal: A Brief Update - Thapa, Shyam (Journal of Nepal Health Research Council, 2021)
Recently revised estimates of levels and trends of maternal mortality based on three sources are reviewed and the trajectory for reaching the mortality reducing target by 2030 is assessed. According to the estimates provided by the UN Maternal Mortality Inter-agency Group (MMEIG), the maternal mortality ratio (MMR) started from a high of 901 in 1990 declined to 258 in 2015, or a reduction of 71% over the 25 year period. Between 2000 and 2015, MMEIG estimates showed a reduction of 53%. The MMR is targeted to be reduced to at least 70 by 2030. This implies a reduction of 73%, which is considerably higher than the reduction recorded during the earlier (2000-2015) period (which was 53%), or annualized rate of decline of 8.7% v 5.0%. Therefore, achieving the future trajectory warrants undertaking strategic interventions more intensively than what may have been hitherto. Concurrently, more attention also needs to be given to strengthening the recording and reporting of maternal deaths.Keywords: levels and trends; maternal mortality; Nepal; projections